Usefulness of Implantation of Diffractive Multifocal Intraocular Lens in Eyes with Long Axial Lengths - Tomoichiro Ogawa; Takuya Shiba; Hiroshi Tsuneoka (Journal of Ophthalmology)
Purpose. This study retrospectively analyzed the postoperative visual functions of myopic eyes implanted with multifocal intraocular lens (IOL) to evaluate the efficacy of multifocal IOL in highly myopic eyes. Methods. We studied 61 patients (96 eyes) who were implanted with multifocal IOL ZMA00 or ZMB00 (Abbott Medical Optics). The patients were stratified into two groups by axial length: 26 mm or above (AL≥26 group) and below 26 mm (AL<26 group). Postoperative corrected and uncorrected distance (5 m) and near (30 cm) visual acuity (VA), contrast sensitivity, and depth of focus were compared between two groups. Results. In the AL≥26 group and the AL<26 group, the mean ± standard deviation uncorrected distance logMAR VA at 12-month postoperative follow-up was -0.04±0.11 and -0.01±0.14, respectively; and the corrected distance VA was -0.17±0.08 and -0.14±0.07, with no significant differences between two groups (p=0.558 and 0.101; Mann-Whitney U test). For near VA, the corresponding uncorrected VA was 0.06±0.08 and 0.05±0.09; and distance-corrected VA was 0.01±0.06 and 0.01±0.02, with no significant differences between two groups (p=0.572, and 0.157; Mann-Whitney U test). Conclusion. The present study demonstrates that it is possible to achieve good uncorrected near and distance VA following implantation of multifocal IOL in eyes with long axial lengths.